Implementation of the Contextual Teaching and Learning (CTL) Learning Model Assisted by Question Card Media in Social Studies Learning for Grade V Students - Sari, Sintia; Yuneti, Armi; Lontoh, Willy (Global Education Journal, 2025)
Social Studies (IPS) education in elementary schools greatly helps students understand their social, cultural, and economic environment. This study aims to determine the achievement of social studies learning outcomes of grade V of SD Negeri 47 Lubuklinggau after the implementation of the Contextual Teaching and Learning (CTL) Learning Model Assisted by Question Card Media. This type of research is quantitative research. With a sample of 25 students of grade VB of SD Negeri 47 Lubuklinggau. Data collection techniques used in this study are tests, observations, interviews and documentation. Data analysis techniques in this study are determining the standard deviation and average, normality test (Chi square) and hypothesis testing (t-test). The results of this study are in the post-test calculation of the hypothesis test can be obtained t count = 1.815 and obtained t table = 1.711. The testing criteria if t count ≥ t table then Ho is rejected and Ha is accepted. If t count ≤ t table then Ho is accepted and Ha is rejected. Based on the calculation of the hypothesis test above, it is obtained that t count ≥ t table (1.815 ≥ 1.711) so Ho is rejected and Ha is accepted. In other words, the hypothesis proposed in this study can be accepted as true, meaning; The learning outcomes of fifth grade students in social studies learning at SD Negeri 47 Lubuklinggau after the implementation of the Contextual Teaching and Learning learning model assisted by Question Card media are significantly complete.